Rescue of death receptor and mitochondrial apoptosis signaling in resistant human NSCLC in vivo - Okouoyo, Stella; Herzer, Kerstin; Ucur, Esat; Mattern, Jürgen; Krammer, Peter H.; Debatin, Klaus-Michael; Herr, Ingrid (International journal of cancer, 2004)
Non small cell lung carcinoma (NSCLC) is a highly lethal malignancy that often becomes resistant to chemotherapy. To determine whether alterations in apoptotic signaling might contribute to such resistance, we established in vitro and in vivo models for sensitive and resistant human NSCLC. We found that resistance is due to multiple defects found in expression of CD95-L, CD95 and members of the Bcl-2 and IAP family, as well as caspase-8, -9 and -3 as examined by immunohistochemistry, Western blot analysis, gene array analysis and functional assays. Failure to activate death receptor, as well as mitochondrial apoptosis signaling, points to a central role of caspases. To restore apoptosis signaling we transfected NSCLC xenografts on nude mice with caspase-8 and -9. This treatment strongly induced apoptosis per se and sensitized the tumors to cisplatin-induced cell death. Thus, these findings indicate that re-expression of caspases might be an effective strategy to restore sensitivity for chemotherapy in NSCLC in vivo. © 2003 Wiley-Liss, Inc.
First published: 05 November 2003
Gesehen am 04.03.2021